PRACTICE-FOCUSED MATHEMATICS EDUCATION FOR O & G STUDENTS AND SPECIALISTS - Liliya R. Zagitova (Высшее образование в России)
This paper presents the practice-focused experience of maths training of oil and gas students and engineers at Almetyevsk State Oil Institute. The author describes the methods to formation of professional maths competences, proposes the structural and functional model of maths training within the system "education - research - production", and views the organizational and pedagogical conditions for its realization.